História de vida e comportamento de risco em amostra brasileira - Rachel Coelho Ripardo; Carla Silva Fiaes; Sâmia de Carliris Barbosa Malhado; Samai Alcira; Eulina da Rocha Lordelo (Arquivos Brasileiros de Psicologia, 2012)
The consequences of risky behavior in a developing country like Brazil requires complex analysis, involving multiple variables, such as those related to life history. Age, civil status, parental status and subjective life expectancy may moderate the perception of risk behavior and its attraction. Thus, the research aimed to identify factors in the history of life related to risky behavior in the Brazilian context. To this end, the scale Risk-propensity Scale was applied in 358 participants over 18 years. The results showed that the dimensions Perception and Attractiveness were impacted by the context and history of life. In general, the younger, unmarried, childless, and the ones that expected to live less tended to perceive as less risky the behaviors and to risk more. These results are consistent with the evolutionary perspective of the life cycle, which submits the behavioral dispositions to the priorities for each age: growth, reproduction and maintenance.